Review of mining flies of the genus Phytobia Lioy (Diptera: Agromyzidae): Western Palearctic species - Zlobin, Vladimir V. (Zootaxa, 2008)
Phytobia pseudobetulivora is described as new to science (type-locality: Tajikistan, Gissar ridge, Kondara ravine). The key for identification of West Palaearctic Phytobia species is provided. New faunistic records are given. The neotype of Agromyza errans Meigen, 1830 is designated.